Uji Aktivitas Sitotoksik dan Antibakteri Ekstrak Daun Tumbuhan Rengas (Gluta renghas L) - Ibrahim, Sanusi; Suryati, Suryati; Aziz, Enda Desriansyah (Jurnal Riset Kimia, 2020)
Generally, Gluta renghas L. is known because of its very toxic latex which can cause hard irritations to skin. Although, rengas latex has efficacy as an antibacterial agent. Related to previous research, it has been reported that there are urisol, rengol, glutarengol, laccol, and thitsiol in rengas latex. The woody trunk was reported to contain flavonoid, benzenoid, lipid, and steroid compounds. The leaves, were reported shows that the leaves of G. renghas contain an anticholinesterase substance and can be reduced the rate of hydrolysis of acetylcholine. Extraction of rengas leaves has been carried out. It has been shown phenols, steroids, and coumarins compounds in methanol extract, flavonoids, phenols, saponins and alkaloids compounds in ethyl acetate extract, steroids and alkaloids compounds in hexane extract. In the present, cytotoxicity and antibacterial activity have been tested. The results show that the great cytotoxicity activity by ethyl acetate extracts which have an LC50 value is 123,718 Âµg/mL (R2 0.9822), while the great antibacterial activity shown by methanol extract 1,000 Âµg/mL with a diameter of inhibition zone 19.02 mm (S. aureus) and 16.06 mm (E. coli).Â